THE MILITARY EDUCATION SYSTEM AS THE FOUNDATION FOR ENSURING THE NATIONAL SECURITY OF THE REPUBLIC OF SERBIA - Bojanić, Dragan; Терзић, Мирослав; Miljković, Milan (Serbian political thought, 2025)
The effective preparation of officer personnel within the Ministry of Defence and the Serbian Armed Forces constitutes a key prerequisite for the successful execution of duties related to the safeguarding of national security. The specific tasks and hierarchical structure of the defense system require that the officer corps – as direct participants in the decision-making process – exert a significant influence on operational efficiency and system functionality. Accordingly, the education and training of officers are of critical importance for the development of their professional competencies, which directly affect the overall level of national security. Contemporary security challenges, the transformation of the nature of modern conflicts, and the evolution of security strategies necessitate reforms aimed at aligning academic curricula with the principles of modern military operations and the demands of the current security environment. This paper presents an empirical study focused on evaluating the applicability of knowledge acquired at the Military Academy in the context of performing officer duties at various hierarchical levels of military decision-making. The research is based on an analysis of the correlation between knowledge obtained through military education and the requirements imposed by operational and tactical military practice. The methodological framework encompasses both quantitative and qualitative data analysis collected through surveys, employing appropriate statistical techniques to determine the extent of the relationship between the educational process and officers’ professional competencies. The findings indicate that officers perceive greater applicability of knowledge acquired through military studies at the tactical level, while at the operational level of decision-making, knowledge from the social sciences is considered relatively more important. These insights contribute to a deeper scientific understanding of the relationship between academic education and military practice, and they provide a foundation for the systematic improvement of curricula with the aim of optimizing the educational process and enhancing its practical relevance.